Wood Sawdust/Natural Rubber Ecocomposites Cross-Linked by Electron Beam Irradiation - Manaila, Elena (Materials (Basel), 2016)
The obtaining and characterization of some polymeric eco-composites based on wood sawdust and natural rubber is presented. The natural rubber was cross-linked using the electron beam irradiation. The irradiation doses were of 75, 150, 300 and 600 kGy and the concentrations of wood sawdust were of 10 and 20 phr, respectively. As a result of wood sawdust adding, the physical and mechanical properties such as hardness, modulus at 100% elongation and tensile strength, showed significant improvements. The presence of wood sawdust fibers has a reinforcing effect on natural rubber, similar or better than of mineral fillers. An increase in the irradiation dose leads to the increasing of cross-link density, which is reflected in the improvement of hardness, modulus at 100% elongation and tensile strength of blends. The cross-linking rates, appreciated using the Flory-Rehner equation, have increased with the amount of wood sawdust in blends and with the irradiation dose. Even if the gel fraction values have varied irregularly with the amount of wood sawdust and irradiation dose it was over 90% for all blends, except for the samples without wood sawdust irradiated with 75 kGy. The water uptake increased with increasing of fiber content and decreased with the irradiation dose.